The financial obligation in international law - Martha, Rutsel Silvestre J. (Oxford Scholarly Authorities on International Law - TRIAL (20 Oct 2020), 2015)
This study concerns international legal obligations, and is thus about substantive law. Substantive law defines rights, duties, and liabilities. It does not encompass either adjectival law, by which substantive law is applied, or `corporate' law of the parties to the obligatory relations.